Найти производные 1)yx=1+x81+x812x12 y’=8×71+x8+1+x88x721+x8∙12×12-144×111+x81+x812x122= =8×71+x8+4×71+x812x12-1+x81+x8x13= =12×71+x812x12-1+x81+x8x13 2) yx=2ex+1+lnex+1-1ex+1+1 y’=exex+1+ex+1+1ex+1-1∙ex∙ex+1+12ex+1-ex∙ex+1-12ex+1ex+1+12= =exex+1+1ex+1=ex+1 3) yx=1+x3arcsinx y’=32x∙arcsinx-1+x3∙11-x2arcsin2x= =3x2arcsinx-1+x3arcsin2x1-x2 4) yx=x∙sinxlnxsinx lny=lnxsinxlnxsinx lny=ln2xsinx

Найти производные.
1)yx=1+x81+x812x12
y’=8×71+x8+1+x88x721+x8∙12×12-144×111+x81+x812x122=
=8×71+x8+4×71+x812x12-1+x81+x8x13=
=12×71+x812x12-1+x81+x8x13

2) yx=2ex+1+lnex+1-1ex+1+1
y’=exex+1+ex+1+1ex+1-1∙ex∙ex+1+12ex+1-ex∙ex+1-12ex+1ex+1+12=
=exex+1+1ex+1=ex+1

3) yx=1+x3arcsinx
y’=32x∙arcsinx-1+x3∙11-x2arcsin2x=
=3x2arcsinx-1+x3arcsin2x1-x2

4) yx=x∙sinxlnxsinx
lny=lnxsinxlnxsinx
lny=ln2xsinx
lny’=ln2xsinx’
y’y=2lnxsinx∙sinx+xcosxxsinx
y’=x∙sinxlnxsinx∙2lnxsinx∙sinx+xcosxxsinx=
=x∙sinxlnxsinx∙2lnxsinx∙1x+ctg x

5) yx=3arcsin34x+1+2×2+2
y’=3∙11-34x+12∙-124x+12+2xx2+2=
=-364x+1216×2+8x-84x+12+2xx2+2=
=-18(4x+1)2(2×2+x-1)+2xx2+2

6) ex+2cosy=xy
yx’=-Fx’Fy’
F=xy-ex+2cosy
Fx’=y-ex+2cosy
Fy’=x-ex+2cosy∙-2siny
yx’=-Fx’Fy’=-y-ex+2cosyx+2sinyex+2cosy

7) xt=tyt=11-t
yx’=yt’xt’
yt’=11-t’=—t21-t3=t21-t3
xt’=t’=12t
yx’=yt’xt’=t21-t3∙2t=t1-t3

8) yx=lncos2x+1+cos4x
y’=1cos2x+1+cos4x∙2cosx-sinx+4cos3x∙-sinx21+cos4x=
=1cos2x+1+cos4x∙cosxsinx-2-2cos2x1+cos4x=
=-2sinxcosx1+cos4x

9) yx=x+7lnx+4, y»»x-?
y’=ln(x+4)+x+7x+4
y»=1x+4+x+4-x-7x+42=1x+4-3x+42
y»’=-1x+42+6x+43
y»»=2x+43-18x+44=2x+8-18x+42=2x-5x+44

10) xt=2t-t2yt=3t-t3, t0=1
Решение.
x1=2-1=1
y1=3-1=2
xt’=2-2t
yt’=3-3t2
yx’=yt’xt’=3-3t22-2t=32(1+t)(1-t)(1-t)=321+t
y0’=32∙2=3
Уравнение касательной:
y-y0=yx’x-x0
y-2=3x-1
y=3x-1
Уравнение нормали:
y-y0=-1y0’x-x0
y-2=-13x-1
y=-x3+213

Решение:

y=3x-1; y=-x3+213.

11) limx→a2-xatgπxa=2-aatgπaa=1tg π=1

limx→1ln2-x1-x=limx→1ln2-x’1-x’=limx→1-12-x-1=limx→112-x=1

limx→∞x5xex=limx→∞x4ex=∞∞=0

12) yx=2x+125-x
y’=22x+15-x-x+1222x+125-x=2x+15-x-x2-2x-12x+125-x=
=10x-2×2+10-2x-x2-2x-12x+125-x=-3×2+6x+92x+125-x=
=-3x+1x-32x+125-x=-3x-325-x

13) yx=-8-x2x2-4
y’=-2xx2-4+8+x2∙2x2x2-4×2-4=
-2xx2-4+8x+x3x2-4×2-4=16x-x3x2-432

14) yx=x2x-12
y’=2xx-12-2x-1∙x2x-14=2×2-2x-2x2x-13=-2xx-13

yx=-1236x-12×2+2x+9
y’=-1236∙233x-1∙x2+2x+9-2x+236x-12×2+2x+92=
=-12 23633x-1×2+2x+9-2x+136x-12×2+2x+92

1 Звезда2 Звезды3 Звезды4 Звезды5 Звезд (Пока оценок нет)
Загрузка...